2008
DOI: 10.1080/10862960802502121
|View full text |Cite
|
Sign up to set email alerts
|

Portrayals of Print Literacy in Children's Television Programming

Abstract: Television continues to be an important part of young children's daily lives. Therefore, an important question lies in how popular television programs depict aspects of children's development and learning, including literacy. Through a content analysis, this study analyzed the top 10 programs for viewers between the ages of 2 and 5 for portrayals of literacy, specifically looking at the amount of and affective qualities of print literacy events in these programs. Print literacy events were defined as any time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…We postulated that RB educational shows would be positively related to literacy outcomes because they are designed around a curriculum to teach a specific academic or socio-emotional lesson. Consistent with this idea, the work of Linebarger and colleagues has shown that Between the Lions promotes basic literacy skills for early readers (e.g., Linebarger, 2000;Linebarger, Kosanic, Greenwood, & Doku, 2003), and several studies have been published that show Reading Rainbow is effective at promoting literacy development (e.g., Moses, 2011;Moses & Duke, 2008). On the other hand, Boohbah and Teletubbies may be labeled as educational-indeed, both of these programs are/were rated as E/I ("educational/informational") on PBS-but they are not produced and created in the same way as RB educational programs.…”
Section: Figure 2 Interaction Between Nrb Programming Consumption Andmentioning
confidence: 91%
“…We postulated that RB educational shows would be positively related to literacy outcomes because they are designed around a curriculum to teach a specific academic or socio-emotional lesson. Consistent with this idea, the work of Linebarger and colleagues has shown that Between the Lions promotes basic literacy skills for early readers (e.g., Linebarger, 2000;Linebarger, Kosanic, Greenwood, & Doku, 2003), and several studies have been published that show Reading Rainbow is effective at promoting literacy development (e.g., Moses, 2011;Moses & Duke, 2008). On the other hand, Boohbah and Teletubbies may be labeled as educational-indeed, both of these programs are/were rated as E/I ("educational/informational") on PBS-but they are not produced and created in the same way as RB educational programs.…”
Section: Figure 2 Interaction Between Nrb Programming Consumption Andmentioning
confidence: 91%